Clonal Evolution Dynamics in Primary and Metastatic Lesions of Pancreatic Neuroendocrine Neoplasms - Tong, Zhou; Wang, Lin; Shi, Weiwei; Zeng, Yanwu; Zhang, Hangyu; Liu, Lulu; Zheng, Yi; Chen, Chunlei; Xia, Weiliang; Fang, Weijia; Zhao, Peng (Frontiers in Medicine, 2021)
Background: Data on inter-tumoral heterogeneity and clonal evolution of pancreatic neuroendocrine neoplasms (panNENs) with liver metastasis are limited. The aim of this study was to explore different patterns of clonal evolution of pancreatic neuroendocrine neoplasms with liver metastasis and the possible distinctive signaling pathways involved between G2 neuroendocrine tumors (NETs) and neuroendocrine carcinomas (NECs). Methods: Tumor tissues of five patients (10 samples) with pancreatic neuroendocrine neoplasms with synchronous liver metastasis were analyzed using next-generation sequencing. PyClone, Gene Ontology, and Reactome pathway enrichment analysis were also applied. Results: Mutated genes varied in individuals, reflecting the inter-tumoral heterogeneity of panNENs. The distribution of subclones varied during tumor metastasis, and different clonal evolution patterns were revealed between NETs and NECs. Gene Ontology and Reactome analyses revealed that in both NETs and NECs, signaling pathways and biological processes shared similarities and differences in the primary and metastatic lesions. In addition, the signaling pathway features were different between NETs and NECs. In the primary lesions, epigenetic changes and post-transcriptional modifications participated in NETs, while FGFR signaling, EGFR signaling, and NTRK2 signaling were largely involved in NECs. Although DNA repair and TP53 regulation were both involved in the metastatic lesions, most of the signaling pathways and biological processes disrupted by the mutated genes were different. Conclusions: Our study revealed spatial inter-tumoral heterogeneity and temporal clonal evolution in PanNENs, providing potential therapeutic targets for further prospective clinical trials.